Maternal care influence on children's caries prevalence in southern Brazil - Gabriela dos Santos PINTO; Andréia Drawanz HARTWIG; Raquel ELIAS; Marina Sousa AZEVEDO; Marília Leão GOETTEMS; Marcos Britto CORREA; Flávio Fernando DEMARCO (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract This study aimed to investigate the influence of specific maternal-factors on caries prevalence in offspring. This cross sectional study was conducted in Pelotas, Brazil nested in a cohort of adolescent mothers with children aged 24-42 months. A questionnaire was administered to collect information in relationship to socio-economic, demographic, and behavioral maternal variables. The outcome (children's dental caries prevalence - dmfs > 0) was collected from clinical examinations. Bivariate and multivariate analyses were conducted. A total of 538 mother/child dyads were evaluated and 15.1% of the children exhibited caries. Adjusted multivariate analysis showed children from mothers living without partners (p < 0.027) had more caries than those living with partners. Maternal perception of a child's oral health was associated to occurrence of caries, particularly when mothers classified their child as poor and these children had a higher level of caries. In addition, mothers accurately evaluated their child's teeth when associated with caries occurrence. Maternal oral health care practices were associated with children's caries prevalence. Our results demonstrated mothers accurately evaluated the oral health of their offspring.